Specific Monitoring the DNA Helicase Function via Anchor‐Embedded DNA Probe - Keni Ning; Xiaoyan Tang; Zhe Li; Liting Zhong; Yingchen Zhou; Jiaen Wang; Wanyi Huang; Han Zhang; Jiajun Ke; Tiangang Luan; Shuo‐Bin Chen; Junqiu Zhai (Advanced Science)
Abstract DNA helicases play a pivotal role in maintaining genome integrity by unwinding the DNA double helix and are often considered promising targets for drug development. However, assessing specific DNA helicase activity in living cells remains challenging. Herein, the first anchor‐embedded duplex (ATED) probe, 17GC, is constructed to uniquely monitor the unwinding activity of Werner syndrome helicase (WRN), a clinical anticancer target. This probe integrates biophysical screening and molecular simulation approaches. The 17GC probe consists of two components: the first one is a bubble structure as an anchor for recruiting WRN in cells, and the second one is GC‐rich double helices on both ends of the bubble, which allow high sensitivity in detecting WRN activity. In vitro evaluations demonstrate that 17GC is highly sensitive and specific to WRN (LOD = 33.5 pm) compared to a wide range of other enzymes, including helicases and nucleases. Cellular evaluation reveals that the ATED probe exhibits remarkable performance in monitoring WRN helicase activity and assessing the inhibitory efficiency of clinical WRN inhibitors in various cell types. This study introduces a novel approach for designing specific and sensitive probes for DNA helicases in cells, which holds promise for biological characterization and drug development.